Hightech as a platform for economic growth - Natalia V. Popova (Цифровое право)
Today, the majority of developed jurisdictions vigorously provide instruments for the focused support of the economic sectors and companies, which are able to give a significant positive effect for the whole economy in the nearest perspective. It is particularly true for the fastest-growing companies, which operate in the tech sectors i.e. technology-based gazelle companies. Such companies manufacture unique products, creates new job places for highly qualified staff and intensively export their tech solutions worldwide. Despite overall reduction of the earnings, some technology-based companies demonstrate outstanding flexibility in searching for the new opportunities and markets in the context of COVID-19 pandemic. However, the majority of technologybased gazelle companies rapidly grow out of the thresholds for the small and medium enterprises. In turn, these companies get into the “death valley” in the absence of the focused instruments of the governmental support. At the same time, complex governmental support in the spheres of tax, financing and procurement is able to promote achievement by the certain technology-based gazelle companies of their potential and make them “unicorn” companies with market value over USD 1 billion and even world leaders in their technology sectors. That, in turn, will give a chance for the growth of the Russian economy even in the context of the fall of the prices on energy resources. This article proposes complex and the most relevant measures of the state support for the technology-based gazelle companies, taking into account the foreign experience and Russian peculiarities.